PENGELOMPOKKAN SEPULUH VARIETAS TEMBAKAU (Nicotiana tabacum) BERDASARKAN KERAGAMAN RUNUTAN BASA PARSIAL GEN PMT(PUTRESCINE N-METHYLTRANSFERASE) Clustering of ten tobacco (Nicotiana tabacum) varieties based on the partial PMT (putrescine N-methyltranfera - Sesanti Basuki; Sudarsono Sudarsono (Jurnal Penelitian Tanaman Industri, 2017)
PMT gene is the gene encoded putrescine N-methiltransferase which is related to nicotine biosinthesis in tobacco (Nicotiana  tabacum). Ten tobacco varieties with different nicotine level were used inthis study. The aims of this study were: (1) to analyze thepartial PMT gene sequence diversity among ten tobacco varieties, and (2) to evaluate the closed-relationship amongten tobacco varieties based on their partialPMT gene sequences diversity.Sequence diversity was analyzed by multiple sequence alignment between the partialPMT gene sequence of the ten tobacco varietiesand Ntpmt_Sindoro1 sequence deposited in the NCBI gene-bank database.The phylogenetic relationship amongthe sequences was inferred by genetic distancebetween pairs of sequences using the pairwise and multiple sequence alignment analysis. Analysis of the sequences showed that all varieties analyzed had varied in size and number of the PMT gene fragments yielded. The analysis also revealed that thepartialPMT gene sequencesarecoming from the same ancestor which related to nicotine biosynthesis in tobacco. Phylogenetic analysis separated the partialPMT gene sequences into two different branches significantly (bootstrap value = 100), and clustered together based on tobacco types with different nicotine level in whichcould be due to some baseschanged on the specific sites of thePMT gene sequences.  This information could be used to study the relationship between some bases changed on the specific sites of thePMT gene sequences and the nicotine content variation yielded by the ten tobacco varieties that is happened during evolution time.Key words: Clustering analysis, PMT gene, nicotine, Nicotiana tabacum AbstrakGen PMT adalah gen penyandi enzim putresina N-metiltransferase (PMT) yang berperan dalam lintasan biosintesis nikotin pada tanaman tembakau (Nicotiana tabacum). Sepuluh varietas tembakau yang memiliki perbedaan tingkat kadar nikotin diuji untuk mempelajari: (1) keragaman runutan basa parsial gen PMT dari masing-masing varietas, dan (2) kekerabatan antara sepuluh varietas tembakau yang diuji berdasarkan keragaman runutan basa parsial gen PMT. Keragaman runutan basa dianalisis dengan mensejajarkan data runutan basa dari sepuluh varietas tembakau yang diuji dengan runutan basa dari Ntpmt_Sindoro1 (JQ438825) yang telah tersimpan dalam database genbank NCBI. Hasil pensejajaran digunakan untuk menghitung matriks jarak, yang selanjutnya digunakan untuk menganalisis hubungan kekerabatan diantara sepuluh varietas tembakau. Hasil analisis memperlihatkan adanya variasi ukuran dan jumlah runutan basaparsial gen PMT asal sepuluh varietas tembakau yang dianalisis. Hasil analisis juga memperlihatkan bahwa runutan basa parsial gen PMT tersebut berasal/diturunkan dari sumber (ancestor) yang sama dan  terkait dengan biosintesis nikotin pada tembakau. Runutan basaparsial gen PMT dari sepuluh varietas yang dianalisis memisahkan antara kelompok tembakau introduksi (kadar nikotin rendah-sedang) dengan kelompok tembakau lokal (kadar nikotin sedang-tinggi). Dua kelompok memisah berdasarkan level kadar nikotin, danperbedaan/perubahan susunan basa pada situs-situs tertentu dari runutan basaparsial gen PMT  yang dianalisis. Informasi tentang mutasi yang terjadi pada situs-situs runutan basa dari parsial gen PMT dapat digunakan untuk mempelajari keterkaitan antara perubahan basa pada fragmen gen PMT dengan kandungan nikotin total tembakau yang terjadi selama proses evolusi.Kata kunci: Analisis pengelompokkan, gen PMT,Nikotin, Nicotiana tabacum